Innovation ecosystems : increasing competitiveness - Fransman, Martin (New York, NY : University of Edinburgh, 2019)
Martin Fransman presents a new approach to understanding how innovation happens, who makes it happen, and the helps and hindrances. Looking at innovation in real-time under uncertainty, he develops the idea of an 'innovation ecosystem', i.e. a system of interrelated players and processes that jointly make innovation happen. Examples include: how companies like Amazon, Google, Facebook, Apple, AT&T, and Huawei interact in the ICT Ecosystem; four innovations that changed the world - the transistor, microprocessor, optical fibre, and the laser; the causes of the telecoms boom and bust of the early 1990s that influenced the Great Recession from 2007; and the usefulness of the idea of innovation ecosystems for Chinese policy-makers. By delving into the complex determinants of innovation this book provides a deeper, more rigorous, understanding of how it happens. It will appeal to economists, social scientists, business people, policy makers, and anyone interested in innovation and entrepreneurship--
Includes bibliographical references and index.
Keywords: Technological innovations; Research, Industrial; Industrial productivity centers